Defining the limits of homology modeling in information‐driven protein docking. Issue 12 (17th October 2013) - Rodrigues, J. P. G. L. M.; Melquiond, A. S. J.; Karaca, E.; Trellet, M.; van, M.; van, G. C. P.; Schmitz, C.; de, S. J.; Bordogna, A.; Bonati, L.; Kastritis, P. L.; Bonvin, Alexandre M. J. J.; et al.
ABSTRACT Information‐driven docking is currently one of the most successful approaches to obtain structural models of protein interactions as demonstrated in the latest round of CAPRI. While various experimental and computational techniques can be used to retrieve information about the binding mode, the availability of three‐dimensional structures of the interacting partners remains a limiting factor. Fortunately, the wealth of structural information gathered by large‐scale initiatives allows for homology‐based modeling of a significant fraction of the protein universe. Defining the limits of information‐driven docking based on such homology models is therefore highly relevant. Here we show, using previous CAPRI targets, that out of a variety of measures, the global sequence identity between template and target is a simple but reliable predictor of the achievable quality of the docking models. This indicates that a well‐defined overall fold is critical for the interaction. Furthermore, the quality of the data at our disposal to characterize the interaction plays a determinant role in the success of the docking. Given reliable interface information we can obtain acceptable predictions even at low global sequence identity. These results, which define the boundaries between trustworthy and unreliable predictions, should guide both experts and nonexperts in defining the limits of what is achievable by docking. This is highly relevant considering that the fraction of the interactome amenable for docking is only bound to grow as the number of experimentally solved structures increases. Proteins 2013; 81:2119–2128. © 2013 Wiley Periodicals, Inc.